Epitaxial Ba2NdFeNb4O15-based multiferroic nanocomposite thin films with tetragonal tungsten bronze structure. (15th July 2017) - Hajlaoui, T.; Chabanier, C.; Harnagea, C.; Pignolet, A.
Abstract: High-quality Ba2 NdFeNb4 O15 -based nanocomposite films were grown on Pt/MgO(100) single crystalline substrates. The c-oriented epitaxial films have the unit cell rotated in the plane by ± 18.5° with respect to that of the substrate. The room temperature ferroelectric properties of the films were demonstrated at both the macroscopic and the microscopic scales, attesting that the macroscopic ferroelectricity was conserved down to the nanoscale. The presence of a small amount of nanocrystalline BaFe12 O19 as a magnetic secondary phase was confirmed by measuring ferromagnetic hysteresis loops. The coexistence of ferroelectric and ferromagnetic phases attested the achievement of nanocomposite films, exhibiting room temperature multiferroic properties. Graphical abstract: